Impact of deicing salts on pervious concrete pavement - Feng, Lichao; Zhang, Yongran; Wang, Xiaowei; Mery, Stephene; Akin, Michelle; Li, Mengchao; Xie, Ning; Li, Zhenming; Shi, Xianming (Frontiers in Materials, 2023)
To meet new federal EPA regulations for minimizing fine silt from the Nevada Department of Transportation (NDOT), a powerful tool should be used. In 2012, the NDOT started building a pervious pavement around Lake Tahoe. Case studies of two pervious concrete projects, SR28 and SR431, were included in this research. Both projects are located in the Lake Tahoe area. Mechanical properties were significantly higher in SR28 cored samples than in SR431 cored samples. Compared to the SR431 models, the SR28 pieces are thicker and have fewer air voids. The SR431 samples have higher water absorption and hydraulic conductivity than the SR28 samples. The SR28 models fare better against repeated freezing and thawing than the SR431 ones. SEM pictures of crack surfaces in cores taken from SR28 and SR431 indicate that the cement binder phase has been largely retained. Needle-shaped residues, on the other hand, can be seen within the cement binder phase of the moderately damaged samples. Extremely distressed pieces typically lack the cement binder phase and an abundance of precipitated micro-sized particles. On a micrometer scale, the μCT examination reveals that the porosity of SR28 samples is significantly less than that of SR431.